Menentukan Luas Daerah Segitiga Spheris - Mulyadi Mulyadi; Mirna Mirna; Riry Sriningsih (UNIVERSITAS NEGERI PADANG, 2021)
Abstract - Spherical Triangle is a triangle on surface of ball that formed by circles which cutting the ball. The circle that forms a Spherical Triangle are circles which cutting the ball in center. Area of Spherical Triangle is different from Euclid Triangle. This study look at how to find the Area of Spherical Triangle. The result obtained in this study is how to find the area of Spherical Triangle that must knows about dihedral angle or trihedral angle that forms spherical triangle.Keywords - spherical triangle, dihedral angle, trihedral angle.